2014
DOI: 10.1186/1471-2393-14-136
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in pregnancy among First Nations women in Alberta, Canada: a retrospective analysis

Abstract: BackgroundIn addition to increasing the risk of adverse birth outcomes, diabetes in pregnancy is thought to be an important driver of the epidemic of type 2 diabetes affecting Canada’s First Nations population. The relative contributions of gestational diabetes mellitus (GDM) and pre-existing diabetes are not well understood. We generated a comprehensive epidemiological profile of diabetes in pregnancy over a 10-year period among the First Nations population of Alberta, Canada.MethodsDe-identified administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
65
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 23 publications
6
65
2
Order By: Relevance
“…From as early as infancy, First Nations children experience substantial exposure to painful events. 35 The current study identified higher rates of NICU admissions among First Nations newborns compared with non-First Nations newborns, and additional research supports this finding. Oster and colleagues found that First Nations newborns were more likely to be admitted to the NICU for hypoglycemia related to maternal diabetes.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…From as early as infancy, First Nations children experience substantial exposure to painful events. 35 The current study identified higher rates of NICU admissions among First Nations newborns compared with non-First Nations newborns, and additional research supports this finding. Oster and colleagues found that First Nations newborns were more likely to be admitted to the NICU for hypoglycemia related to maternal diabetes.…”
Section: Discussionsupporting
confidence: 75%
“…Oster and colleagues found that First Nations newborns were more likely to be admitted to the NICU for hypoglycemia related to maternal diabetes. 35 Research conducted in Canadian NICUs indicates newborns undergo an average of 11 painful procedures per day, 38 and infants with hypoglycemia require frequent blood sampling for glucose monitoring. 39 High rates of ear and dental condition diagnoses were evident in this study's First Nations cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chamberlain et al . noted in one study where Australian indigenous women had a higher age‐adjusted GDM prevalence compared with non‐indigenous women at 6.3% versus 2.4% that was similar to results from a population‐based study conducted in Alberta, Canada, with reported rates of 6.1% versus 3.8%, respectively. In addition, Chamberlain et al .…”
supporting
confidence: 72%
“…By contrast, the second algorithm based on the presence of gestational diabetes-specific ICD-9/10 codes during the delivery hospitalization, was associated with more acceptable sensitivity, specificity and positive predictive values of 86, 99 and 85%, respectively. Perhaps as a result of changing maternal characteristics, including older age and obesity, the rates of gestational diabetes are increasing [18,19]. Although gestational diabetes is generally a temporary condition and resolves postpartum, it is an established risk factor for the subsequent development of Type 2 diabetes [7,8].…”
Section: Discussionmentioning
confidence: 99%